Hip arthroplasty for acute hip fracture in patients with neurological disorders: A report Of 9, 702 cases from the Swedish arthroplasty register. Issue 3 (March 2022) - Wojtowicz, Alex L.; Al-Azzani, Waheeb; Nåtman, Jonatan; Rolfson, Ola; Rogmark, Cecilia; Cnudde, Peter H.J.
Highlights: A neurological disorder was identified in just under a quarter of patients undergoing arthroplasty for an acute hip fracture. Patients with these neurological disorders were at increased risk of dislocations and AE's, but not at increased risk of reoperation or revision. As any dislocation is bothersome for the patient, we used the total dislocation rate as outcome measure in addition. Abstract: Introduction: The purpose of this study was to investigate neurological disorder as a risk factor for dislocation following arthroplasty for acute hip fractures. We also analysed medical and surgical adverse events (AE), readmission, reoperation, revision, and mortality as secondary outcomes. Methods: A longitudinal cohort study using prospectively collected and aggregated data from the Swedish Hip Arthroplasty Register (SHAR) and the Swedish national patient register. All patients presenting with an acute hip fracture and treated with an arthroplasty in the period from 2005 to 2014 from the SHAR were identified. Patients in receipt of bilateral arthroplasties were excluded. Patients with a relevant pre-existing and diagnosed neurological disorder, as defined by ICD-10 codes, were identified ( n  = 9, 702). All other cases ( n  = 29, 411) were available for logistic regression propensity score matching. Patients were 1:1 matched on age, sex, Charlson comorbidity index, total versus hemiarthroplasty, head size, surgical approach, and year of surgery. Dislocations, adverse events, readmission, reoperation, revision, and mortality were studied using Kaplan-Meier analysis and Cox regression. Results: The risk of dislocations was higher for patients with neurological disorder (HR=1.19, CI 1.03- 1.39, p <0.05). Neurological disorder was associated with increased risk of encountering an adverse event ( p <0.001 at 90-days); these patients were at higher risk of dying (HR=1.51, CI 1.47–1.56, p <0.001) however they were less likely to be readmitted (HR=0.73, CI 0.70- 0.76, p <0.001). No excess risks of reoperation (HR=1.02, CI 0.90–1.17; p  = 0.73) or revision (HR=1.00, CI 0.86–1.17; p  = 0.99) were identified in the study group. Discussion: Compared to matched controls, individuals with a preoperatively identified neurological diagnosis had higher rates of mortality, dislocations, and adverse events, but this cohort was not at increased risk of reoperation or revision. This study highlights an area of focus for future research to improve the long-term outcomes in patients with neurological disease undergoing arthroplasty for an acute hip fracture.